Human Hepatic HepaRG Cells Maintain an Organotypic Phenotype with High Intrinsic CYP450 Activity/Metabolism and Significantly Outperform Standard HepG2/C3A Cells for Pharmaceutical and Therapeutic Applications. Issue 1 (15th July 2016) - Nelson, Leonard J.; Morgan, Katie; Treskes, Philipp; Samuel, Kay; Henderson, Catherine J.; LeBled, Claire; Homer, Natalie; Grant, M. Helen; Hayes, Peter C.; Plevris, John N.
Abstract: Conventional in vitro human hepatic models for drug testing are based on the use of standard cell lines derived from hepatomas or primary human hepatocytes (PHHs). Limited availability, interdonor functional variability and early phenotypic alterations in PHHs restrict their use, whilst standard cell lines such as HepG2 lack a substantial and variable set of liver‐specific functions such as CYP450 activity. Alternatives include the HepG2‐derivative C3A cells selected as a more differentiated and metabolically active hepatic phenotype. Human HepaRG cells are an alternative organotypic co‐culture model of hepatocytes and cholangiocytes reported to maintain in vivo ‐like liver‐specific functions, including intact Phase I–III drug metabolism. In this study, we compared C3A and human HepaRG cells using phenotypic profiling, CYP450 activity and drug metabolism parameters to assess their value as hepatic models for pre‐clinical drug testing or therapeutics. Compared with C3As, HepaRG co‐cultures exhibit a more organotypic phenotype, including evidence of hepatic polarity with the strong expression of CYP3A4, the major isoform involved in the metabolism of over 60% of marketed drugs. Significantly greater CYP450 activity and expression of CYP1A2, CYP2E1 and CYP3A4 genes in HepaRG cells (comparable with that of human liver tissue) was demonstrated. Moreover, HepaRG cells also preferentially expressed the hepatic integrin α5 β1 – an important modulator of cell behaviour including growth and survival, differentiation and polarity. Drug metabolite profiling of phenacetin (CYP1A2) and testosterone (CYP3A4) using LC‐MS/MS and HPLC, respectively, revealed that HepaRGs had more intact (Phase I–II) metabolism profile. Thus, HepaRG cells significantly outperform C3A cells for the potential pharmaceutical and therapeutic applications.